Synthesis, In Silico and In vivo Evaluation of Novel 1, 3, 4-Thiadiazole Analogues as Novel Anticancer Agents - Krishna, Swathi; Gowramma, Byran; Mohammed, Manal; Kalirajan, Rajagopal; Kaviarasan, Lakshman; Praveen, Thaggikuppe K. (Letters in Drug Design & Discovery, 2020)
Background: 1,3,4-thiadiazole is a lead molécule which is versatile for a wide variety of biological activities and in continuation of our interest in establishing some novel heterocyclic compounds for antitumor activity. Objective: The objective of the study was to synthesize series of 5-(1,3-benzodioxol-5-yl)-1,3,4- thiadiazol-2-amine derivative and evaluated for their possible in vitro and in vivo anticancer activity. Methods: The synthesis of 2-aminonaphthoxy-1,3,4-thiadiazole and 5-(1,3-benzodioxol-5-yl)-1,3,4- thiadiazol-2-amine as intermediates were carried out by cyclization method. A mixture of thiosemicarbazide and naphthoxyacetic acid/piperonylic acid and phosphoryl chloride were subjected to cyclization with phosphorous oxychloride to obtain compound 3. Further compounds 1 and 3 were reacted with different aromatic aldehydes in methanol to form compounds 2a-e and 4a-e. The compounds 2a-e and 4a-e were characterized for the melting points, IR, Proton NMR and Mass spectra. The compounds were further evaluated for their anticancer activity. The docking study was performed using Discovery studio 4.1 (Accelrys) software against DNA-binding domain of STAT3. The compounds were analyzed for the ligand-protein binding interaction(s) by molecular docking into the active site of STAT3β using the CDOCKER protocol of Discovery studio (v4.1). Results: The title compounds were screened for in vitro anticancer on human breastadenocarcinoma cells (MCF-7 and Vero). Compounds 4c, 4d and 2d against MCF 7 and 4d against Vero cell lines were found to be the most active dérivatives with IC50 values of 1.03, 2.81 and 3.45 μg/ml against MCF 7 and 31.81 μg/ml against Vero cell lines, respectively. Conclusion: From the in vivo anticancer studies, it was concluded that the synthesized compounds 4c and 4d displayed anticancer activity comparable to the standard drug, while the rest of the compounds demonstrated mild potency for anticancer studies.
Keywords: MCF-7